Vibration analysis of wing - Chen, Jian. (2008)
The objectives are to investigate the vibration problems on fixed wing structure in different displacement modes in order to provide a combination view on wing structure vibration and to study the frequency domain vibration characteristics by examining the vibration frequency versus various key wing structure parameters.